2001
DOI: 10.1093/humrep/16.7.1489
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic resection of submucosal myomas in patients with infertility

Abstract: Hysteroscopic myomectomy appears safe, and is effective in the control of menstrual disorders. However, the effect on infertility seems limited, particularly in terms of delivery rate. The advanced age of the patients may partly explain these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 18 publications
5
55
1
12
Order By: Relevance
“…The incidence of submucosal myomas in women during their reproductive age ranges from 20 to 25 % [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of submucosal myomas in women during their reproductive age ranges from 20 to 25 % [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Most of submucosal myomas may induce severe clinical symptoms such as abnormal uterine bleeding and menorrhagia with an incidence ranging from 60 to 84 % [3], dysmenorrehea , and infertility [1,2,4,5]. The hysteroscopic treatment of this pathology has shown to be effective in relieving symptoms and in improving on the patients' fertility [6].…”
Section: Introductionmentioning
confidence: 99%
“…13 Other studies also concluded that hysteroscopic leiomyoma resection also improves fertility rates, especially when tumors are the sole cause of infertility. [14][15][16] Even uterine artery embolization is an angiographic interventional procedure that delivers particulate emboli into both uterine arteries. Uterine blood flow is therefore obstructed, producing ischemia and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesions around salpinges could result from subserosal myomas [15]. The distortion and enlargement of the endometrial cavity by submucous and intramural fibroids with an intracavitary component can affect the implantation [19,20]. Implantation is also affected by vascular disturbances and inflammation of the endometrium and secretion of vasoactive substances [16,21].…”
Section: Fibroids and Infertilitymentioning
confidence: 99%